Meningkatkan Kecerdasan Kinestetik pada Anak Usia Dini Melalui Outbound pada Siswa RA Al-Ghifary - Hartin Kurniawati; Ika Rahayu Satyaninrum; Siskha Putri Sayekti; Putri Rahmizar (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
This research begin from the importance of development that must be had in early childhood, namely aspects of cognitive development, motor development and language development, and social-emotional. The purpose of this study was to determine the increase in kinesthetic intelligence in early childhood using the outbound method. The research method used was Classroom Action Research (PTK) which was carried out through 2 cycles with each cycle of stages being Planning, Action, Observation and Reflection. The subjects of this study were RA Al-Ghifary Class B students for the 2022-2023 academic year, with a total of 25 students. Data collection was carried out using observation data and interviews and documentation. The results of the research show 1) Cycle I percentage is 60.6%, Cycle 2 reaches 87.8%, 2) children's kinesthetic intelligence can be increased by outbound methods such as carrying out coordinated body movements to train flexibility, balance and agility, then coordinate eye movements chief accomplices in imitating dance or gymnastics, performing physically according to the rules, skillfully using the right and left hands, carrying out personal hygiene activities. In addition, outbound games are outdoor activities whose purpose is to relax and unwind, with relatively light series of adventures and games.